Relationship between serum inflammatory markers and vascular function in a cohort of adolescents with type 1 diabetes. (November 2017) - Sochett, Etienne; Noone, Damien; Grattan, Michael; Slorach, Cameron; Moineddin, Rahim; Elia, Yesmino; Mahmud, Farid H.; Dunger, David B.; Dalton, Neil; Cherney, David; Scholey, James; Reich, Heather; et al.
Abstract: Objective: The contribution of inflammation to endothelial/vascular dysfunction in early Type I Diabetes (T1D) is not well understood. The objective of this study was to examine the interaction between systemic inflammation and vascular function in adolescent's with and without-T1D. Methods: 51 subjects from our observational cohort of adolescents with T1D (JDRF-CCTN), and 59 healthy controls (HC) were studied. Serum cytokines-chemokines were quantified using Human 41-Plex Array, and vascular function was measured by Flow Mediated Dilatation (FMD), Pulse Wave Velocity (PWV) and Blood Pressure (BP). Factor Analysis was used to identify pro- and anti-inflammatory cytokine-chemokine factors, which were then correlated with vascular outcomes. Results: Three pro-inflammatory factors were identified in HC and three in TID, and a single anti-inflammatory factor in both groups. In HC there was a positive correlation (r = 0.33; p = 0.01) between control proinflammatory Factor 1 and systolic BP and a negative correlation between control proinflammatory Factor 3(r = −0.29; p = 0.02) and diastolic BP. Control proinflammatory Factor 2 correlated positively with PWV. In TID subjects, no correlations were found between any of the pro-inflammatory factors and the vascular measurements. No correlations were found between the anti-inflammatory factors and BP, FMD and PWV in either HC or T1D. Levels of pro-inflammatory analytes, EGF, GRO, PDGF-BB, PDGF-AA and sCD40L were significantly higher in T1D. Conclusions: The cytokine-chemokine signature in early T1D, prior to the development of arterial disease, is significantly different from that seen in healthy controls. This may be relevant to pathophysiology, determining risk and identifying target cytokines-chemokines for intervention in T1D.